HUBUNGAN AKSESIBILITAS DAN TINGKAT PENDAPATAN MASYARAKAT TERHADAP TINGKAT PENDIDIKAN DI KENAGARIAN SURIAN KECAMATAN PANTAI CERMIN KABUPATEN SOLOK - Medrawati, Medrawati; Suarto, Edi; Keslan, Widya Prari (STKIP PGRI Sumbar, 2013)
This study aims to determine the accessibility and level relations income society against education level in Kenagarian Surian Pantai Cermin district Solok region.The study was correlation descriptive. The population is all households that are in Kenagarian Surian Surian Pantai Cermin district Solok region, amounting to 3,518 households. Samples were taken in two ways, the sample region taken with the sampling technique purvosive 5 taken as representative of the whole ellipse ellipse that is based on consideration of the large number of households, while the sample of respondents proportional random sampling technique with a proportion of 10% for the sample areas so that the sample of respondents totaled 196 KK.The research found that: 1) There is a relationship between the level of accessibility and education at Kenagarian Surian Pantai Cermin district Solok regionfor t> t table (2.150> 1.645), very low power relationship (r = 0.153) and a very small contribution (2.3% ), (2) There is a relationship between the level of income by education level in Kenagarian Surian Pantai Cermin district Solok region for t> t table (8.626> 1.645), the strength of the relationship being (r = 0.527) and a small contribution (27.7%) and ( 3) There is a significant relationship between accessibility and the level of income together with the level of education in Kenagarian Surian Pantai Cermin district Solok regionbecause Fhitung> F table (38.618> 2.751), relationship between the two variables with the level of education in the district Surian Kenagarian Kenagarian Surian Pantai Cermin district Solok regionincludes medium category (r = 0.535) and a small contribution (28.6%).